Dr. Antonios Koumouridis — Deep Plane Facelift — Oslo - Koumouridis, Antonios (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Antonios Koumouridis, practicing in Oslo, Norway. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003336; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; norway; oslo